(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
The proposed transformation of the global geoid model method for the determination of the local geoid model of Nigeria has only been applied in part of the Federal Capital Territory, Abuja. To determine the consistency of the accuracy of the method for the intended purpose, there is a need to apply it in some other parts of the country. As a result, this study presents the verification of the consistency of the proposed transformation of global geoid method accuracy for local geoid model of Nigeria determination. DGNSS observations were carried out to obtain the coordinates of the used points. The processed global geographic coordinates were used with online software (GeoidEval) to obtain the EGM 08 geoid heights of the points. The global geographic coordinates, the global geoid heights of the points and the transformation parameters from WGS 84 to Minna datum were applied to obtain the transformed (local) geoid heights of the points using a Microsoft Excel program. The transformed geoid heights were compared with their corresponding geoid heights from the gravimetric-geometric local geoid model of the study area to obtain the model RMSE (accuracy). The obtained accuracy (2.0172 m) was compared with those of the gravimetric-geometric geoid model of the study area (0.675 m) and the transformation of global geoid heights when the method was applied in part of Abuja (0.0014 m). The comparison results showed the inconsistency of the accuracy of the proposed method. It is recommended that the method should not be applied for the intended purpose.